Experience with a synthetic bilayer biodegradable temporising matrix in complex wounds - Shah, Sankit D.; Shah, Ankit N.; Ghelani, Nilesh B.; Shah, Virank V.; Godhani, Chintan A.; Pathak, Nupoor H. (International Journal of Research in Medical Sciences, 2025)
Bilayer Biodegradable Temporising Matrix (BTM) is a synthetic polyurethane dermal matrix used to reconstruct complex wound with exposed bone and tendon, chronic wound. We hope to further explore its potential applications in this series. Patients who received BTM application across our centres over a 12-months period were included. Patients were followed up to assess BTM and graft take, substitute for flap in small wound, stable coverage, cover in trophic ulcer and prevent recurrence. A total 15 patients with wounds were identified with a range of aetiologies. wounds had 100% integration of BTM at the time of sealing membrane removal. Two wounds had partial graft loss that later healed by secondary intention. BTM offers a safe and reliable reconstructive option in challenging wounds that would otherwise require more complex operations.